Effect of compaction energy on engineering characteristic of compacted soil - Muhammad Ikram, Bin Uzir Abdul Wahab. (Universiti Malaysia Sarawak, UNIMAS, 2010)
Soil compaction is a significant stage in construction. When field compaction is performed improperly, soil excessive settlement could occur and result in unnecessary maintenance costs or structure failure. The objective for this research is to study the effect of compaction energy to compaction characteristic of granular soil. Granular soil is widely used as a replacement soil when dealing with soft soil such as peat and very soft clay. Furthermore, granular soil is commonly used in pavement of runaway which requires strong base to sustain heavy load from vehicles. Compactive effort is one factor that affects the quality of compaction. Standard and Modified Proctor had been used to show the effect of compactive effort to the river sand and laterite soil samples. The study proved that the maximum dry density of soils increases when the compactive effort increases which also contributed to higher shear strength.